1994
DOI: 10.1016/0735-1097(94)90496-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of intravenous heparin in conjunction with anistreplase (anisoylated plasminogen streptokinase activator complex) in acute myocardial infarction: The Duke University clinical cardiology study (DUCCS) 1

Abstract: Weight-adjusted intravenous heparin therapy after APSAC in acute myocardial infarction does not reduce the combined incidence of death, reinfarction, recurrent ischemia and occlusion of the infarct-related artery. Furthermore, withholding intravenous heparin therapy is associated with a 46% reduction in bleeding complications. Our findings do not support the addition of intravenous heparin after APSAC therapy, as currently recommended, and suggest that a strategy of withholding heparin is simpler and safer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 45 publications
0
15
1
1
Order By: Relevance
“…Concealment of treatment allocation appeared adequate in the 3 studies that reported this. 42,43,45 Two of the 4 studies were double-blind and placebo controlled, 43,44 and follow-up was complete in the 1 study that reported this. 42 …”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Concealment of treatment allocation appeared adequate in the 3 studies that reported this. 42,43,45 Two of the 4 studies were double-blind and placebo controlled, 43,44 and follow-up was complete in the 1 study that reported this. 42 …”
Section: Study Qualitymentioning
confidence: 99%
“…39,40 Clinical outcome data could not be obtained for 1 additional study, 41 leaving 14 randomized trials, involving a combined total of 25 280 patients, for inclusion in the meta-analysis (Tables 1 to 3). 11,[42][43][44][45][46][47][48][49][50][51][52][53][54] Table 1 summarizes the study designs. [42][43][44][45] Two studies used streptokinase, 42,44 1 alteplase, 43 and 1 anistreplase.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a small difference in coronary artery patency (80% in the heparin group versus 74% in the control group). 148 Two large trials, the International Study Group 149 and the ISIS-3 150 (International Study of Infarct Survival) studies, assessed the value of adjunctive heparin in patients receiving thrombolytic therapy and aspirin. In both, heparin was given (12 500 U SC every 12 hours).…”
Section: Coronary Thrombolysismentioning
confidence: 99%
“…The intravenous administration of unfractionated heparin (UFH) is the only anti-coagulant treatment currently recommended as an adjunct to fibrin-specific thrombolytics for the treatment of ST-elevation acute myocardial infarction (STEMI) [1, 2], in order to improve early recanalization and reduce reocclusion and reinfarction rates [3,4,5,6,7,8,9,10,11,12]. UFH, however, has several pharmacokinetic (i.e.…”
Section: Introductionmentioning
confidence: 99%